Enhanced antitumor efficacy of fiber‐modified, midkine promoter‐regulated oncolytic adenovirus in human malignant mesothelioma. Issue 11 (23rd September 2013) - Takagi‐Kimura, Misato; Yamano, Tomoki; Tamamoto, Atsuko; Okamura, Nobutaka; Okamura, Haruki; Hashimoto‐Tamaoki, Tomoko; Tagawa, Masatoshi; Kasahara, Noriyuki; Kubo, Shuji
Abstract : Oncolytic virotherapy using adenoviruses has potential for therapeutic benefits in malignant mesothelioma. However, the downregulation of coxsackie virus/adenovirus receptor (CAR) expression is frequently a critical rate‐limiting factor that impedes the effectiveness of adenovirus serotype 5 (Ad5)‐based vectors in many cancer types. We evaluated CAR (Ad5 receptor) and CD46 (adenovirus serotype 35 [Ad35] receptor) expression in six human malignant mesothelioma cell lines. Very low CAR expression was observed in MSTO‐211H and NCI‐H2052 cells, whereas the other cell lines showed strong expression. In contrast, CD46 was highly expressed in all mesothelioma cell lines. On this basis, we replaced the CAR binding sequence of Ad5 with the CD46 binding sequence of Ad35 in the replication‐defective adenoviruses and the tumor‐specific midkine promoter‐regulated oncolytic adenoviruses. By this fiber modification, the infectivity, virus progeny production, and in vitro cytocidal effects of the adenoviruses were significantly enhanced in low CAR‐expressing MSTO‐211H and NCI‐H2052 cells, also resulting in similar or even higher levels in high CAR‐expressing mesothelioma cell lines. In MSTO‐211H xenograft models, the fiber‐modified oncolytic adenovirus significantly enhanced antitumor effect compared to its equivalent Ad5‐based vector. Our data demonstrate that Ad35 fiber modification of binding tropism in a midkine promoter‐regulated oncolytic Ad5 vector confers transductional targeting to oncolytic adenoviruses, thereby facilitating more effective treatment of malignant mesothelioma.